2017
DOI: 10.3389/fpls.2017.01037
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Repertoire of Necrotrophic Fungal Phytopathogen Ascochyta rabiei: Predominance of MYB Transcription Factors As Potential Regulators of Secretome

Abstract: Transcription factors (TFs) are the key players in gene expression and their study is highly significant for shedding light on the molecular mechanisms and evolutionary history of organisms. During host–pathogen interaction, extensive reprogramming of gene expression facilitated by TFs is likely to occur in both host and pathogen. To date, the knowledge about TF repertoire in filamentous fungi is in infancy. The necrotrophic fungus Ascochyta rabiei, that causes destructive Ascochyta blight (AB) disease of chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 83 publications
(111 reference statements)
0
41
0
Order By: Relevance
“…In this study, the MYB gene family of P. ostreatus was analyzed at the genome-wide level . P. ostreatus has 20 MYB genes, which is more than that of Magnaporthe oryzae (13), Botrytis cinerea (15), Ascochyta rabiei (16), and Fusarium graminearum (19) [ 56 ], and less than that of Neurospora crassa (36) and Laccaria bicolor (37) [ 57 ]. The size of the MYB gene family of P. ostreatus is smaller than those of plants, but larger than those of animals, which generally comprise four or five MYBs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the MYB gene family of P. ostreatus was analyzed at the genome-wide level . P. ostreatus has 20 MYB genes, which is more than that of Magnaporthe oryzae (13), Botrytis cinerea (15), Ascochyta rabiei (16), and Fusarium graminearum (19) [ 56 ], and less than that of Neurospora crassa (36) and Laccaria bicolor (37) [ 57 ]. The size of the MYB gene family of P. ostreatus is smaller than those of plants, but larger than those of animals, which generally comprise four or five MYBs [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 323 putative effectors with no known protein domain and 70 proteins of the predicted secretome showed sequence similarity to members of the Pathogen-Host Interaction (PHI) database (Winnenburg et al 2006) with annotated involvement in virulence or pathogenicity (Verma et al 2016). In addition to proposed virulence proteins, transcription factors that control gene expression during plant infection by A. rabiei have been predicted for ArD2 and assessed for their contribution to pathogenesis (Verma et al 2017). Verma et al (2017) suggest that for A. rabiei, Myb transcription factors play a role in regulating the expression of genes encoding secreted proteins, such as effectors.…”
mentioning
confidence: 99%
“…In addition to proposed virulence proteins, transcription factors that control gene expression during plant infection by A. rabiei have been predicted for ArD2 and assessed for their contribution to pathogenesis (Verma et al 2017). Verma et al (2017) suggest that for A. rabiei, Myb transcription factors play a role in regulating the expression of genes encoding secreted proteins, such as effectors. Gene regulation by transcription factors during plant infection may also vary depending on specific isolate and host interactions (Verma et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, genes M_11_12_v1_01448 and M11_12_v1_01460 are both likely transcription factors with Pfam domains including the Myb-like DNA binding domain and the Zn(2)-Cys(6) binuclear cluster domain, respectively. Previous research has shown that transcription factors with the Myb-like DNA binding domain regulate the secretome in necrotrophic fungal pathogen [31] and a transcription factor with the Zn(2)-Cys(6) binuclear cluster domain has a key role in regulating virulence in a fungus infecting wheat [32]. The cytochrome P450 gene, M11_12_v1_01466, is a member of a large group of genes that was found to be present in the M. phaseolina genome in high numbers and may be associated with secondary metabolites and overcoming hose defenses [1].…”
Section: Discussionmentioning
confidence: 99%